Pendidikan Nilai Spiritual dalam Prosesi Hijrah Nabi Muhammad SAW ke Madinah - Zulfatmi Zulfatmi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
This paper presents spiritual values and spiritual value education practices in the procession of the Prophet Muhammad's migration to Medina. These values are extracted from the Sirah Nabi text written in the book "The Life of Muhammad" by Muhammad Husain Haekal. By using the analytical-descriptive history method, the selected sirah texts were analyzed using the semiotic-narrative model. The spiritual values found are the spiritual values of amali in the form of strategic intelligence; careful; strong keep secrets; trust; dzikr; and pray. Meanwhile the spiritual value of maqamy is raja’ '(hopeful); patient; ta'at (obey); and tawakkal. Included in the spiritual values of ahwali are muraqabah (being alert or feeling watched); and yaqin (true belief). The value education practice shown by the Prophet in the description of the text is a value education practice that is very nice, integral and comprehensive. Apik (nice) means that the value education process takes place neatly and systematically from the internalization of a certain spiritual value to the next spiritual value. Integral is characterized by value education activities integrated into the routine activities of preaching and the daily activities of the Prophet Muhammad as part of the community. While comprehensive, it is seen that the goal of the Prophet's spiritual value education practice is comprehensive both for friends and foes. The methods of internalizing values vary in the form of teaching, modeling, habituation, disciplining, developing values and facilitating the ease of value internalization.